2020
DOI: 10.22219/jrak.v10i2.11820
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Environmental, Social and Governance (ESG) Disclosure on Firm Performance: The Role of Ceo Tenure

Abstract: This paper aims to investigate the effect of environmental, social, and governance (ESG) disclosure on firm performance, which is measured by ROE. We also analyze the role of CEO tenure on the relationship between ESG disclosure and ROE. We used 159 samples of public listed companies in Indonesia during period of 2012 to 2016. We employed multiple regression technique to assess the research model. The findings show that ESG disclosure has a positive impact on ROE. The better the quality of ESG disclosure can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
1
15
1
8
Order By: Relevance
“…Social accounting believes that the company's optimal performance can also be measured from environmental and social aspects (Deegan, 344: 2014). Companies with good environmental and social performance will gain legitimacy and a positive response from the public (Triyani et al, 2020). Therefore, there is a shift in the focus of accounting reporting.…”
Section: Introductionmentioning
confidence: 99%
“…Social accounting believes that the company's optimal performance can also be measured from environmental and social aspects (Deegan, 344: 2014). Companies with good environmental and social performance will gain legitimacy and a positive response from the public (Triyani et al, 2020). Therefore, there is a shift in the focus of accounting reporting.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [1] using data of 159 Indonesian companies from 2012 to 2016 the authors found out that ESG disclosure has a positive impact on return on equity. The higher the disclosure quality the higher ROE.…”
Section: Results Of Papermentioning
confidence: 99%
“…A large layer of research is dedicated to study of the interrelation between ESG and financial indicators. From the point of view of the stakeholder theory and the legitimacy theory a company should pay attention to values and norms existing in the society where it operates [1]. It is of crucial importance because recognition by the community is used as the factor which may influence corporate stability.…”
Section: Interrelation Between Esg Indicators and Financial Indicator...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of ESG disclosure is still a debate among researchers whether ESG disclosure can improve firm performance. Research conducted by Albitar et al (2020) and Triyani et al (2020) found results that ESG will improve and has positive impact on firm performance, but these results are contradictory to Junius et al (2020) and Fatemi et al (2018) that found ESG had no effect on firm performance. In response to that, firm orientation is starting to shift from being profit oriented to stakeholder oriented that more aware towards environmental and social responsibility.…”
Section: Introductionmentioning
confidence: 84%